2017
DOI: 10.1021/acsnano.6b07531
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Energy Efficiency and Polarity Control in Germanium Nanowire Transistors by Individually Gated Nanojunctions

Abstract: Germanium is a promising material for future very large scale integration transistors, due to its superior hole mobility. However, germanium-based devices typically suffer from high reverse junction leakage due to the low band-gap energy of 0.66 eV and therefore are characterized by high static power dissipation. In this paper, we experimentally demonstrate a solution to suppress the off-state leakage in germanium nanowire Schottky barrier transistors. Thereto, a device layout with two independent gates is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 40 publications
2
52
0
Order By: Relevance
“…Further skewing into one or the other direction can be achieved by using source and drain materials with different workfunctions to each other, in order to obtain a work function offset between source and drain contact, as already explored in 2-D Materials [26], [27]. Beyond this, it has been demonstrated that germanium and silicon-germanium channel materials further reduce V TH and increase the on-currents of MIGFETs [28], [29]. Another very straightforward improvement is to apply the clock signal not to a gate aligned on-top of the Schottky barrier, but to one of the channel gates, which perform slightly better even under skewed conditions, as discussed earlier in this section.…”
Section: A Device Level Performance Enhancementsmentioning
confidence: 99%
“…Further skewing into one or the other direction can be achieved by using source and drain materials with different workfunctions to each other, in order to obtain a work function offset between source and drain contact, as already explored in 2-D Materials [26], [27]. Beyond this, it has been demonstrated that germanium and silicon-germanium channel materials further reduce V TH and increase the on-currents of MIGFETs [28], [29]. Another very straightforward improvement is to apply the clock signal not to a gate aligned on-top of the Schottky barrier, but to one of the channel gates, which perform slightly better even under skewed conditions, as discussed earlier in this section.…”
Section: A Device Level Performance Enhancementsmentioning
confidence: 99%
“…We target the design of standard-cell libraries for emerging devices with enhanced functionality. To showcase our method, we have chosen the Germanium-based reconfigurable field effect transistor (RFET) from [13] as an exemplary technology. Transistor reconfiguration switches a transistor between Pand N-type carrier transport dynamically [1]- [4], [13].…”
Section: Related Workmentioning
confidence: 99%
“…To showcase our method, we have chosen the Germanium-based reconfigurable field effect transistor (RFET) from [13] as an exemplary technology. Transistor reconfiguration switches a transistor between Pand N-type carrier transport dynamically [1]- [4], [13]. Additionally, multiple gates are used to intrinsically support the AND-functionality, as demonstrated for a similar technology based on Silicon [5], [14].…”
Section: Related Workmentioning
confidence: 99%
“…Several RFETs have been experimentally demonstrated based on bottom-up grown Si or Ge nanowires [7]- [11], carbon nanotubes [12] or two-dimensional materials [13]- [16]. Low band-gap channel materials like Ge are beneficial to increase the current close to CMOS levels [17].…”
Section: Introductionmentioning
confidence: 99%